2018
DOI: 10.1111/jopr.12943
|View full text |Cite
|
Sign up to set email alerts
|

Implant Placement under Existing Removable Dental Prostheses and the Effect on Follow‐Up and Prosthetic Maintenance

Abstract: The therapeutic concept of implant placement under existing prostheses was promising when performed in indicated cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…The reasons behind this result could be that the few fixed crowns might relieve a patient’s frustration caused by tooth loss, and the support and retention provided by implants used as surveyed crowns in the IC-RPDs may help patient mastication. In a previous study on IODs, not only subjective chewing ability but also objectively measured chewing efficiency was improved based on a test diet [ 45 ]. In our study, only one patient in the IOD group reported discomfort and a decrease in masticatory force, and we assumed that this was because their IOD was made to salvage failed fixed full implant prostheses.…”
Section: Discussionmentioning
confidence: 99%
“…The reasons behind this result could be that the few fixed crowns might relieve a patient’s frustration caused by tooth loss, and the support and retention provided by implants used as surveyed crowns in the IC-RPDs may help patient mastication. In a previous study on IODs, not only subjective chewing ability but also objectively measured chewing efficiency was improved based on a test diet [ 45 ]. In our study, only one patient in the IOD group reported discomfort and a decrease in masticatory force, and we assumed that this was because their IOD was made to salvage failed fixed full implant prostheses.…”
Section: Discussionmentioning
confidence: 99%
“…IARPDs should have strategic implant distribution to avoid undesirable occlusal forces, and in this regard, opposing arch's situation may determine the clinical performance of both abutments and prostheses [43]. Five articles reported the use of RPDs, fixed partial dentures, or complete dentures in opposing arch [15,23,24,[28][29][30]. However, due to the heterogeneity of obtained data, the influence of opposing arch could not be analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…IODs are relatively easy to adapt to and have a high masticatory efficiency because support and retention can be obtained by placing a small number of implants under the dentures [ 6 ]. Marotti et al suggested that the therapeutic concept of implant placement under existing prostheses is promising when performed in indicated cases [ 33 ]. Dependent elderly patients with mandibular dentures can benefit from the insertion of dental implants, providing adequate oral healthcare and aftercare by caregivers.…”
Section: Discussionmentioning
confidence: 99%
“…Patients should be advised of their role in maintenance, and a comprehensive recall system is mandatory to obtain satisfactory long-term results [ 35 ]. Other studies have also reported that retention loss of the attachment system is the most frequent complication [ 33 , 36 ].…”
Section: Discussionmentioning
confidence: 99%